Analysis of the Quality of Nursing Services According to Hospital Accreditation 2012 Version, Reviewed from Baldrige Malcolm Criteria in Pasar Minggu Jakarta Selatan Hospital in 2017 - Edi Wahyudi, R; Yulianty Permanasari, V (KnE Life Sciences, 2018)
The nursing services as an integral part of health services in hospitals are required to provide quality services according to standards. One of the standards used in the assessment of nursing services in Indonesia is Hospital Accreditation Version 2012 that assesses nursing service in eight standard chapters. There are several quality measurement models proven to be effective in quality management, one of which is the Malcolm Baldrige Criteria. This hospital is based on the Hospital Accreditation Version 2012, reviewed from Malcolm Baldrige Criteria as preparation for accreditation and continuous quality improvement. This research is descriptive-analytic research with a qualitative approach through an in-depth interview of key informants, document review, observation, and focus group discussion. The results found that the implementation of nursing service standards according to the Hospital Accreditation Version 2012, especially the Patient and Family Chapter, the Patient and Family Education Chapter, and the Infection Prevention and Control Chapter have passed the minimum requirement of 80% achievement targets. Position Quality Score of Nursing Services Division at Pasar Minggu Hospital according to Hospital Accreditation Version 2012 reviewed from Malcolm Baldrige Criteria is on score 555.75, which is in ‘Good Performance’ predicate, indicating ‘Average’ quality level. The Nursing Services Division at Pasar Minggu Hospital can develop opportunities for improvement in senior leadership and strategy development criteria. Keywords: Malcolm Baldrige, accreditation, hospital, nursing services